ازدواجی تعلقات کی سماجی و نفسیاتی جہات: ایک تجزیہ: Socio-Psychological Aspects of Marital Relationship: An Analysis - Aajiza, Tasneem; Munir, Prof. Dr. Mohsina (Al-Amīr Research Journal for Islamic Studies, 2024)
Today, from the individual to the spouses, parents, children, even the whole family is suffering from depression, anxiety, despair and uncertainty. Domestic life is devoid of mutual love; individuals and families live in houses like they live in hotels, Unknown to each other. When the human being sent as Allah's vicegerent on earth, became guilty of negligence and left the way of Allah (which was the way of welfare and salvation for him) he became a victim of despair and hopelessness and suffered from psychological diseases like depression and anxiety. These facts that destroy a person’s individuality are the result of psychological problems. Therefore, reforming the external life of a human being as well as his spiritual life is very important in the present era. So that the humanity can get rid of the diseases it is suffering from. We have tried to review in this article that what are the causes of the growing psychological problems of men and women at familial level? In this regard, we have obtained the material from authentic sources by doing research and analysis in Islamic perspective. Key Words: Family, Marital Life, psychological problems, Islamic perspective.